2018
DOI: 10.4236/ajor.2018.86027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm for Scattered Storage Assignment in Kiva Mobile Fulfillment System

Abstract: Scattered storage means an item can be stored in multiple inventory bins. The scattered storage assignment problem based on association rules in Kiva mobile fulfillment system is investigated, which aims to decide the pods for each item to put on so as to minimize the number of pods to be moved when picking a batch of orders. This problem is formulated into an integer programming model. A genetic algorithm is developed to solve the large-sized problems. Computational experiments and comparison between the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Kim et al [23] addressed the ISAP to maximize the relevance of items on the pods, and the movement distance of the pods is reduced by the re-optimization algorithm. Guan and Li [24] studied the problem of decentralized storage allocation of items based on association rules in RMFS, aiming to determine the pods on which each item is placed to minimize the number of pods that need to be moved when picking a batch of orders. Tey proposed an integer programming model and developed a genetic algorithm to solve the problem.…”
Section: Te Study Of Isap In Rmfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [23] addressed the ISAP to maximize the relevance of items on the pods, and the movement distance of the pods is reduced by the re-optimization algorithm. Guan and Li [24] studied the problem of decentralized storage allocation of items based on association rules in RMFS, aiming to determine the pods on which each item is placed to minimize the number of pods that need to be moved when picking a batch of orders. Tey proposed an integer programming model and developed a genetic algorithm to solve the problem.…”
Section: Te Study Of Isap In Rmfsmentioning
confidence: 99%
“…Terefore, Pc/Pm � {0.8/0.2} is applicable in this paper. Te hyperparameter settings are also the same with Guan and Li [24]. Te optimization solver Gurobi is used to verify the correctness of the J-IPSAP model and the efectiveness of IGA.…”
Section: Comparative Analysis With Gurobi Optimization Solutions Inmentioning
confidence: 99%
“…They also find that carefully determining the number of picking stations is essential to maintain a high picker utilisation while avoiding congestion. Guan and Li (2018) derive association rules from historical demand data to decide which items to store together on a shelf, to maximise item similarity (the probability that items from the same shelf are ordered together) within the context of scattered storage. They propose a non-linear MIP and a genetic algorithm to solve Robotic Mobile Fulfillment Systems: a Mathematical Modelling Framework for E-commerce Applications CIRRELT-2020-42 it, and they obtain a higher item similarity of about 35%, but their results are not converted to actual productivity gains through simulations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have shown that the correlation between goods, the probability that they appear in the same order at the same time, makes it possible to improve the efficiency of picking through storage planning (Chen HP and Huang Y2021;Guan M and Li Z 2018). In addition, the frequency of selection of goods is affected by the heat of sale.…”
Section: Introductionmentioning
confidence: 99%